(untitled) (AYUSHDHARA, 2018)
The pharmaceutical science is closely related with life science. Knowledge of pharmaceutics is an essential element in medical practice and is the basis for the discovery of new medicines. Before going through preparations of any drug, one has to concentrate on all the matters related to that particular drug like, collection of raw drugs, tests about genuineness of it, different process of prevention and purification, special methods of mixing and so on. Thus pharmaceutical standardization of Ayurvedic medicines is necessary to ensure quality, safety and efficacy of drugs. Among different preparation of formulations, Khalviya rasayana is a basic procedure applicable to all Rasaoushadis before they are subjected to any specific procedure. It converts crude drugs macro to micro level by trituration and also gives specific Samskara to a drug. Panchavaktra Ras is a rational combination of Rasadravyas and Kasthaushadhis. Panchavaktra rasa has been taken for its Pharmaceutical standardization through Standard Operative procedures. The raw drugs Parada, Gandhaka, Tankana are taken and subjected to purification as per Rasatarangini 5/34-35, 8/13-17 and 13/77-78 respectively. Parada, Gandhaka, Tankana, Pippali, Maricha and Krishna Dhattura Swarasa is added in sufficient quantity. In pharmaceutical study the drug has been prepared in 3 batches adopting Khalviya Rasayana method. The final drug prepared in the pharmacy at the weight of 150 mg. The final product of the drug and all the raw drugs were analyzed before and after the purifications with modern analytical methods viz. XRD, ICP-OES, AAS, SEM with EDX, HPTLC, Physico-Chemical Standards, Pharmaceutical Standards, Preliminary Organic Analysis, and Estimation of Microbial Contamination.